Exploring the Impact of Mindfulness on Work Engagement in the Education Sector - Nida Hasanati; Shabiq Azizatul Anisa (AL-ISHLAH: Jurnal Pendidikan, 2024)
The research aims to investigate how mindfulness impacts work engagement through the lens of meaningfulness at work. The research aims to be beneficial for the scientific field of organisational psychology and can serve as a valuable resource for organisations looking to manage human resources from a positive psychology standpoint. This research uses a quantitative approach with a non-experimental research design, and is a type of correlational research. This study is about human resources professionals who work in the education field. Quota sampling is the method used for the sample. Also, subjects were chosen from teachers at all levels, from elementary to high school, with as many topics as possible coming from 150 teachers. The Mindful Attention Awareness Scale (MAAS), the Utrecht Work Engagement Scale (UWES), and the Work and Meaning Inventory (WAMI) scale are the three types of study tools that have been shown to be valid and reliable. A study of 150 teachers in East Java found that mindfulness had a significant negative effect on work participation through meaningful mediation. This effect was 47.8%. When the teacher's mindfulness is low, work engagement will be high, and when it's high, mindfulness will be low, work engagement will be high. There are a lot of things that can change the effects of these three variables. Some of these are teacher welfare, which includes benefits, salary, and job security, and teaching experience, which is linked to the number of years worked as a teacher.